Impaired Glutamatergic Neurotransmission in the Ventromedial Hypothalamus May Contribute to Defective Counterregulation in Recurrently Hypoglycemic Rats - Chowdhury, Golam M.I. (Diabetes, 2017)
The objectives of this study were to understand the role of glutamatergic neurotransmission in the ventromedial hypothalamus (VMH) in response to hypoglycemia and to elucidate the effects of recurrent hypoglycemia (RH) on this neurotransmitter. We 1) measured changes in interstitial VMH glutamate levels by using microdialysis and biosensors, 2) identified the receptors that mediate glutamate’s stimulatory effects on the counterregulatory responses, 3) quantified glutamate metabolic enzyme levels in the VMH, 4) examined astrocytic glutamate reuptake mechanisms, and 5) used (1)H-[(13)C]-nuclear magnetic resonance (NMR) spectroscopy to evaluate the effects of RH on neuronal glutamate metabolism. We demonstrated that glutamate acts through kainic acid receptors in the VMH to augment counterregulatory responses. Biosensors showed that the normal transient rise in glutamate levels in response to hypoglycemia is absent in RH animals. More importantly, RH reduced extracellular glutamate concentrations partly as a result of decreased glutaminase expression. Decreased glutamate was also associated with reduced astrocytic glutamate transport in the VMH. NMR analysis revealed a decrease in [4-(13)C]glutamate but unaltered [4-(13)C]glutamine concentrations in the VMH of RH animals. The data suggest that glutamate release is important for proper activation of the counterregulatory response to hypoglycemia and that impairment of glutamate metabolic and resynthetic pathways with RH may contribute to counterregulatory failure.